Memprediksi Minat Turnover Karyawan PT Danamas Insan Kreasi Andalan ( PT Dika) Yogyakarta - Rhio Zifri Kantataqwa; Purbudi Wahyuni; Sri Dwi Ari Ambarwati (Strata Business Review, 2023)
This research aims to analyze the factors that influence the employee turnover intentions of PT Danamas Insan Kreasi Andalan (PT Dika) Yogyakarta. By using quantitative research methods involving 70 respondents, this research's multiple linear regression analysis showed that work stress and work compensation have a positive and significant influence on turnover intention among PT Danamas Insan Kreasi Andalan (PT DIKA) employees. Apart from that, the work environment also acts as a moderating variable that strengthens the relationship between work stress and turnover intention, as well as between work compensation and turnover intention. These results emphasize the importance of paying attention to work environmental factors in managing work stress and providing work compensation to reduce the intention to change jobs among PT DIKA employees, especially in Yogyakarta. In this way, companies are expected to focus more on improving employee welfare and creating a conducive work environment to reduce turnover risk.